Heterocyclic compounds as antiviral drugs: Synthesis, structure–activity relationship and traditional applications - dos Santos, Giovanny Carvalho [UNESP]; Martins, Lucas Michelão [UNESP]; Bregadiolli, Bruna Andressa [UNESP]; Moreno, Vitor Fernandes [UNESP]; da Silva-Filho, Luiz Carlos [UNESP]; da Silva, Bruno Henrique Sacoman Torquato (Wiley, 2021)
A virus outbreak challenges the economic, medical, and public health infrastructure worldwide. More than one virus capable of triggering diseases have been identified per year since 1972, which requires the development of new ways of treatment and prevention, however, such processes are not rapid and easy. With the pandemic scenario experienced since early 2020, several drugs with well-known purposes have gained prominence, due to speculation of their use in the treatment against the new coronavirus. Among the main drugs studied, the vast majority contain a heterocyclic structure. In this review, we presented the traditional and efficient synthesis of 15 drugs that have been studied for the COVID-19 treatment, containing in their structure heterocycles like indole, quinoline, pyrimidone, tetrahydrofuran, pyrrolidine, triazole, pyridazine, pyrazole, pyrrolopyrimidine, azetidine, pyrrolotriazine, pyrazine, tetrahydropyran, benzofuran, spiroketal, and thiazole. Furthermore, we have shown the original applications, as well as their structure–activity relationship and what is their situation as a drug candidate against COVID-19. Thus, the objective was to consolidate the main synthetic and pharmacological aspects involving clinically developed heterocycles that at some point were presented as promising against SARS-CoV-2.
Keywords: antiviral; heterocycles; SAR; synthesis